Pelatihan Pembelajaran Berbasis Game Online pada Guru Tk As-Salam Kota Malang - Wahyu Irianto; Harits Ar Rosyid; Muhammad Akbar; Febrianto Alqodri (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
The COVID-19 pandemic that has been experienced throughout the world has resulted in the decline of several aspects, ranging from health, the economy, and the education system. Education that usually runs offline (offline) must now be replaced with online (online). Offline learning is different from online learning. A significant differentiator is the media in the learning process. Not all teachers can use technology optimally for the online learning process, especially for kindergarten teachers (TK) As Salam Malang. In the learning process, motivation is needed because if you do not be motivated in learning, it is impossible to carry out learning activities. So there needs to be an innovation or learning breakthrough that makes kindergarten students enthusiastic and feel comfortable from the learning process, namely the online-based game Edu candy. This community service activity aims to provide training for kindergarten teachers who are expected to increase knowledge, especially in the field of technology for As Salam Kindergarten teachers and can improve interesting online learning models so that the material presented by the teacher can be well received by students. Pandemi COVID-19 yang dialami seluruh dunia mengakibatkan terpuruknya beberapa aspek, mulai dari kesehatan, perekonomian, dan juga sistem pendidikan. Pendidikan yang biasanya berjalan secara luar jaringan (luring) kini harus digantikan dengan dalam jaringan (daring). Cara pembelajaran luring berbeda dengan pembelajaran daring. Pembeda yang signifikan adalah media dalam proses pembelajaran. Tidak semua guru bisa menggunakan secara maksimal teknologi untuk proses pembelajaran daring terutama pada guru Taman Kanak kanak (TK) As Salam Malang. Dalam proses belajar, motivasi sangat diperlukan karena jika tidak mempunyai motivasi dalam belajarnya tidak mungkin melakukan aktivitas belajar. Maka perlu adanya sebuah inovasi atau terobosan pembelajaran yang membuat murid-murid TK antusias dan merasakan kenyamanan dari proses belajar tersebut yaitu berbasis game online Educandy. Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan pelatihan terhadap guru TK yang diharapkan dapat menambah pengetahuan khususnya bidang teknologi pada guru TK As Salam dan dapat meningkatkan model pembelajaran yang menarik secara daring sehingga materi yang disampaikan guru dapat diterima baik oleh murid.